The effect of chronic disease warning statements on alcohol-related health beliefs and consumption intentions among at-risk drinkers - Jongenelis, Michelle; Pratt, Steve; Slevin, Terry; Chikritzhs, Tanya; Liang, W.; Pettigrew, Simone (Oxford University Press, 2018)
Informing drinkers of the health risks associated with alcohol consumption via warning statements located on alcohol products can increase their capacity to make healthier choices. This study assessed whether exposing at-risk drinkers to warning statements relating to specific chronic diseases increases the extent to which alcohol is believed to be a risk factor for those diseases and influences consumption intentions. Australians drinking at levels associated with long-term risk of harm (n = 364; 72% male) completed an online survey assessing their drinking habits, beliefs in the link between alcohol and various diseases and drinking intentions. Respondents were then exposed to one of five statements advising of the potential risks associated with alcohol consumption (either cancer, liver damage, diabetes, mental illness or heart disease). Beliefs and drinking intentions were reassessed. Significant increases in the extent to which alcohol was believed to be a risk factor for diabetes, heart disease, mental illness and cancer were found. With the exception of the liver damage and heart disease statements, exposure to each statement was associated with a significant reduction in consumption intentions. Warning statements advising of the specific chronic diseases associated with alcohol consumption can produce favourable changes in drinking intentions among at-risk drinkers.